Aportes para el conocimiento de la dentición del hombre fósil de Baradero (Ameghiniana, 2013)
An X-ray study of the dental pieces of "the man from Baradero" formerly looked upon as a very ancient elelnent of the Pampean formation confirms Martin's conclusions stated at the time of its description it is morphologically identical with the pre-historical and proto-historical aborigenes. Moreover, a new revision discards the pro-Eskimoid group created by Mochi and assigns the various elements to the Lagoa Santa race.